The 4P Marketing Mix Strategy in Sales of Used Clothes (Thrifting) in Banda Aceh City - Nadia Salsabillah; Sarah Nadia (Journal Informatic, Education and Management (JIEM), 2025)
Basically​ sale clothes used Already fulfil indicator sell buy namely that which is of a nature transparency or honesty, clear products offered and according to the price. This research conducted at 4 ( four ) stores sale clothes former which is located in the city of Banda Aceh. This research aiming For know what is the mix strategy marketing that the owner does so that product or his efforts can developing in society. As for the types study This use approach qualitative descriptive with use technique purposive sampling and techniques data collection through interviews, observations and documentation. Research results show that fourth shop thrifting in Banda Aceh City is implemented aspect mix marketing product in aspect variation product as well as still notice quality products sold​ will but consumer tend buy clothes used No based on with existence factor goods branded (branded), then in aspect mix marketing price in aspect pattern determination price fourth shop give same answer​ with price sell started from IDR. 10,000 – IDR. 30,000 and notice price competitive with product competitors and provide discount or piece price with technique specified by the owner​ effort , then in aspect mix marketing fourth promotion shop promote the goods through social media with dominant Instagram and Tiktok applications in form activity promotion is one of them offer COD (cash on delivery) feature where the result can increase sales. Then in aspect mix marketing fourth place shop own location and access strategic shop​ will but only One shop that is Opibeauty which provides land parking.